2021
DOI: 10.3389/fmed.2021.640785
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Preadmission Metformin Use and Outcomes in Intensive Care Unit Patients With Sepsis and Type 2 Diabetes: A Cohort Study

Abstract: Background: Sepsis is a deadly disease worldwide. Effective treatment strategy of sepsis remains limited. There still was a controversial about association between preadmission metformin use and mortality in sepsis patients with diabetes. We aimed to assess sepsis-related mortality in patients with type 2 diabetes (T2DM) who were preadmission metformin and non-metformin users.Methods: The patients with sepsis and T2DM were included from Medical Information Mart for Intensive Care -III database. Outcome was 30-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
77
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(79 citation statements)
references
References 33 publications
1
77
0
1
Order By: Relevance
“…This may explain the results in the previous study ( 32 ) that the plasma concentration of lactic acid in surviving patients was higher than that in dying patients. Reciprocally, in our study, creatinine and lactate concentrations were not significantly different in patients with and without metformin ( 14 18 , 21 , 22 ). Additionally, increasing evidence was provided to show that metformin could ameliorate the autophagy and mitochondrial function of T-cells ( 33 ) and improve the systematic inflammation via decreased pro-inflammatory factors, such as NF-κB and tumor necrosis factor alpha (TNF-α) ( 34 ).…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…This may explain the results in the previous study ( 32 ) that the plasma concentration of lactic acid in surviving patients was higher than that in dying patients. Reciprocally, in our study, creatinine and lactate concentrations were not significantly different in patients with and without metformin ( 14 18 , 21 , 22 ). Additionally, increasing evidence was provided to show that metformin could ameliorate the autophagy and mitochondrial function of T-cells ( 33 ) and improve the systematic inflammation via decreased pro-inflammatory factors, such as NF-κB and tumor necrosis factor alpha (TNF-α) ( 34 ).…”
Section: Discussionsupporting
confidence: 60%
“…The eligible studies were observational studies that included septic patients with DM who used preadmission metformin. Furthermore, three articles ( 16 , 17 , 21 ) showed 28 day mortality, four studies ( 18 , 19 , 22 , 23 ) reported 30 day mortality, and four studies ( 14 , 15 , 24 , 25 ) reported in-hospital mortality. The primary outcome data were extracted.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All the analyses were conducted using the statistical software packages R (http://www.R-project.org, The R Foundation) and Free Statistics software version 1.3 [15]. The complex multistage strati ed sampling design of NHANES was illustrated by the use of appropriate strata, clusters, and weights in the statistical analysis process.…”
Section: Discussionmentioning
confidence: 99%
“…All the analyses were performed with the statistical software packages R ( http://www.R-project.org , The R Foundation), Free Statistics software version 1.3 ( 18 ), and EmpowerStats ( http://www.empowerstats.com ). Comparisons of serum vitamin D levels in participants with diabetes and participants without diabetes were performed between low magnesium intake and high magnesium intake.…”
Section: Methodsmentioning
confidence: 99%